RNA-Seq Profiling of Circular RNAs and the Oncogenic Role of circPVT1 in Cutaneous Squamous Cell Carcinoma - Chen, Shuang (Onco Targets Ther, 2020)
BACKGROUND: Cutaneous squamous cell carcinoma (CSCC) is associated with a poor 5-year survival rate. circRNAs have an important role in a number of physiological and pathological processes. However, the relationship between circRNAs and cutaneous squamous cell carcinoma (CSCC) is unclear. PURPOSE: The aim of the present study was to investigate the expression of circRNAs in cutaneous squamous cell carcinoma (CSCC) and its effect on CSCC proliferation and metastasis. METHODS: We used high-throughput sequencing (RNA-seq) to identify circRNAs that were differentially in CSCC tissue and their paracarcinoma tissue. Quantitative real-time PCR results confirm deep-sequencing findings in CSCC tissue and cell lines. CCK-8 assay and flow cytometry were used to detect the effect of circPVT1 on the proliferation and migration of CSCC cells. RESULTS: We identified 449 circRNAs that were differentially expressed between CSCC and normal adjacent tissue samples. circPVT1 (hsa_circ_0001821) was further researched to confirm its oncogene role in CSCC. CONCLUSION: Differentially expressed circular RNA plays an important role in the development of CSCC, and circPVT1 may be an important target for the treatment of CSCC.